Device-assessed physical activity and sleep quality of post-COVID patients undergoing a rehabilitation program - Iris Poppele; Marcel Ottiger; Michael Stegbauer; Torsten Schlesinger; Katrin Müller (BMC, 2024)
Abstract Background An infection with SARS-CoV-2 can lead to persistent symptoms more than three months after the acute infection and has also an impact on patients' physical activity behaviour and sleep quality. There is evidence, that inpatient post-COVID rehabilitation can improve physical capacity and mental health impairments, but less is known about the change in physical behaviour and sleep quality. Methods This longitudinal observational study used accelerometery to assess the level of physical activity and sleep quality before and after an inpatient rehabilitation program. The study sample consists of 100 post-COVID patients who acquired COVID-19 in the workplace. Group differences related to sex, age, COVID-19 severity, and pre-existing diseases were also analysed. Results Level of physical activity and sleep quality didn't increase after rehabilitation. Overall, there is a high extent of inactivity time and poor sleep quality at both measurement points. Regarding group differences, male patients showed a significantly higher inactivity time before rehabilitation, and younger patients (< 55 years) spend significant more time in vigorous physical activity than older patients. Post-COVID patients with pre-existing cardiovascular, respiratory, and metabolic disease show slightly less physical activity than post-COVID patients without these comorbidities. Female patients and younger patients showed better sleep quality in some sleep parameters at both measurement points. However, no differences could be detected related to COVID-19 severity. Conclusions Ongoing strategies should be implemented to address the high amount of inactivity time and the poor sleep quality in post-COVID patients.